Enhanced algorithms for three-dimensional object interpreter - Haron, Habibollah (2004)
In designing an engineering product during the conceptual stage, freehand sketch plays an important role in conveying engineers' ideas. Solutions on the problems of representing, interpreting and reconstructing the sketch have been of research interest for several decades. The aim of this study is to propose enhanced algorithms to be used to interpret and reconstruct a sketch, and then to produce a threedimensional model. The methodology used in this study is based on the framework of a sketch interpreter that contains three phases. In the first phase, two algorithms were proposed. The first is enhanced thinning algorithm that is used to thin the sketch while maintaining its topology and basic shape. The second is the modified Freeman chain code algorithm that is used to produce chain code series that represented a thinned binary image of the sketch. In the second phase, a new computational comer detection algorithm is proposed to analyse the chain code series to produce two-dimensional geometry entities of the sketch in which the irregular line drawing is transformed into . regular line drawing. In the third phase, a new method to solve a linear system is proposed in whch the regular line drawing is converted into three dimensional model by guessing the depth of each junction. The linear system consists of three image regularities, namely, spatial structure, gradient space, and skewed symmetry. The linear system is solved using bisection method of total least square approximation. Besides reducing the number of image regularities used and new method to solve the linear system, this study has proposed better solutions in terms of an enhanced thinning algorithm, a modified Freeman chain code algorithm as picture description language, and a new computational comer detection algorithm.